Efficacy of proton pump inhibitor therapy for eosinophilic oesophagitis in 630 patients: results from the EoE connect registry. Issue 5 (17th July 2020) - Laserna‐Mendieta, Emilio J.; Casabona, Sergio; Guagnozzi, Danila; Savarino, Edoardo; Perelló, Antonia; Guardiola‐Arévalo, Antonio; Barrio, Jesús; Pérez‐Martínez, Isabel; Lund Krarup, Anne; Alcedo, Javier; de la Riva, Susana; Rey‐Iborra, Esther; et al.
Summary: Background: Proton pump inhibitors (PPIs) are the most commonly used first‐line therapy for patients with eosinophilic oesophagitis (EoE). However, many aspects related to PPIs in EoE are still unknown. Aims: To assess the effectiveness of PPI therapy for EoE in real‐world practice. Methods: This cross‐sectional study collected data on PPI efficacy from the multicentre EoE CONNECT database. Clinical remission was defined as a decrease of ≥50% in dysphagia symptom score; histological remission was defined as a peak eosinophil count below 15 eosinophils per high‐power field. Factors associated with effectiveness of PPI therapy were identified by binary logistic regression multivariate analyses. Results: Overall, 630 patients (76 children) received PPI as initial therapy (n = 600) or after failure to respond to other therapies (n = 30). PPI therapy achieved eosinophil density below 15 eosinophils per high‐power field in 48.8% and a decreased symptom score in 71.0% of patients. More EoE patients with an inflammatory rather than stricturing phenotype accomplished clinico‐histological remission after PPI therapy (OR 3.7; 95% CI, 1.4‐9.5); as well as those who prolonged treatment length from 8 to 12 weeks (OR 2.7; 95% CI, 1.3‐5.3). After achieving clinico‐histological remission of EoE, PPI dosage reduction was effectively maintained in 69.9% of patients, but tended to be less effective among those with a stricturing phenotype. Conclusions: Inflammatory EoE phenotype and treatment duration up to 12 weeks correlated with greater chance for inducing remission of EoE. A stricturing phenotype decreased response rates to PPI therapy both initially and in the long term.